Proceedings of the Twelfth International Conference on World Wide Web - WWW '03 2003
DOI: 10.1145/775152.775207
|View full text |Cite
|
Sign up to set email alerts
|

Towards a multimedia formatting vocabulary

Abstract: C e n t r u m v o o r W i s k u n d e e n I n f o r m a t i c a INS Information Systems INformation SystemsTowards a multimedia formatting vocabulary J.R. van ABSTRACTTime-based, media-centric Web presentations can be described declaratively in the XML world through the development of languages such as SMIL. It is difficult, however, to fully integrate them in a complete document transformation processing chain. In order to achieve the desired processing of data-driven, time-based, mediacentric presentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Examples of such systems include Cuypers [16], Multimedia for You (MM4U) [21], Web, Adaptation, and Multimedia (WAM) [13], and Media Spatial Temporal and Interactive (MSTI) [17]. Cuypers uses a number of processing steps (e.g., semantic structure and quantitative constraints) to generate the final presentation.…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…Examples of such systems include Cuypers [16], Multimedia for You (MM4U) [21], Web, Adaptation, and Multimedia (WAM) [13], and Media Spatial Temporal and Interactive (MSTI) [17]. Cuypers uses a number of processing steps (e.g., semantic structure and quantitative constraints) to generate the final presentation.…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…These approaches require the utilization of declarative languages. An extensive study on the topic can be found in [7]. The Different Capabilities requirement has been researched in [8], although in some simple cases CSS and XSLT are viable alternatives [3].…”
Section: Platformmentioning
confidence: 99%